2014
DOI: 10.1021/ja503150x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Heterogeneity in Transmembrane Amyloid Precursor Protein Homodimer Is a Consequence of Environmental Selection

Abstract: The 99 amino acid C-terminal fragment of amyloid precursor protein (C99), consisting of a single transmembrane (TM) helix, is known to form homodimers. Homodimers can be processed by γ-secretase to produce amyloid-β (Aβ) protein, which is implicated in Alzheimer’s disease (AD). While knowledge of the structure of C99 homodimers is of great importance, experimental NMR studies and simulations have produced varying structural models, including right-handed and left-handed coiled-coils. In order to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 59 publications
9
56
0
Order By: Relevance
“…In contrast, the structure of C99 28−55 homodimer in DPC micelle is a right-handed coiled-coil in agreement with our simulation results of C99 15−55 homodimer in DPC micelle (23,24). These studies raise critical questions related to the peptide environment, focusing on how factors such as micelle size and interfacial curvature might influence peptide structures (25,26).…”
supporting
confidence: 88%
“…In contrast, the structure of C99 28−55 homodimer in DPC micelle is a right-handed coiled-coil in agreement with our simulation results of C99 15−55 homodimer in DPC micelle (23,24). These studies raise critical questions related to the peptide environment, focusing on how factors such as micelle size and interfacial curvature might influence peptide structures (25,26).…”
supporting
confidence: 88%
“…In addition, MD simulations have revealed subtle differences in the ligand-bound conformations of the ECD (Sanders et al, 2013), and domain II has recently been identified as a potential mediator of subtle differences in ligand binding and specific receptor states (Bessman et al, 2014). Further, mutations in the JM-A region alter the energetics of ligand binding to the ECD (Macdonald-Obermann and Pike, 2009), and there is clear evidence that the active conformation of the EGFR TM is flexible and capable of adopting multiple conformation (Endres et al, 2013), like other single pass TM domains (Dominguez et al, 2014). Taken together, these observations support a model in which different ligand-dependent JM-A conformations result from three distinct ligand-bound ECD conformations that are transmitted faithfully through the membrane-sequestered TM helical dimer.…”
Section: Discussionmentioning
confidence: 99%
“…In another study a multiscale approach employing coarse-grained MARTINI followed by all-atom MD simulations allowed the identification of the homodimer structure of two C-terminal fragments of amyloid precursor protein (C99) in the POPC bilayer and the DPC micelle. 570 Carpenter and co-workers performed coarse-grained MD simulation of the tetramerization of four transmembrane helices forming the transmembrane domain of influenza A M2 channel protein. 571 Comparison with the X-ray and NMR structures of the M2 bundle suggests that the resulting model may correspond to a closed state of the channel.…”
Section: Membrane Proteinsmentioning
confidence: 99%